A C-degron regulates Chk1 kinase by allowing stability of inactive Chk1 and by making it short- lived upon activation - Jang-Hyun Oh; Ju-Yeon Hyun; Shun-Jia Chen; Alexander Varshavsky (Proceedings of the National Academy of Sciences, 2026)
The Arg/N-degron pathway of Saccharomyces cerevisiae is mediated by two interacting E3 ubiquitin ligases, Ubr1 and Ufd4. We show here that the mitotic checkpoint kinase Chk1 bears a C-degron that can be recognized by both Ubr1 and Ufd4. Ubr1 is an E3 that can target both N-degrons and C-degrons. Deleting 4 residues from the C terminus of full-length Chk1 1-527 abrogates the bulk of Ubr1/Ufd4 affinity for the resulting Chk1 1-523 , inhibits its polyubiquitylation and degradation, and arrests cell growth. Toxicity of the 4-residue C-terminally (Ct)-deleted Chk1 1-523 was traced to its kinase activity, since the kinase-inactive C h k 1 D 142 A 1 - 523 was nontoxic. The L506R mutation is known to activate Chk1 kinase in a way that bypasses other Chk1 activation pathways. Both kinase-active and kinase-inactive Chk1 proteins that contained the L506R mutation ( C h k 1 L 506 R 1 - 527 and C h k 1 D 142 A , L 506 R 1 - 527 ) were short-lived in vivo, in contrast to wildtype Chk1 1-527 . Furthermore, the catalytic N-terminal (Nt) domain of Chk1 physically interacted with its Ct-domain. These and other results strongly suggested the following mechanism of Chk1 regulation. Ct-residues of Chk1 1-527 are a part of its C-degron, targeted by Ubr1/Ufd4 E3s. But the Ct-domain of Chk1 1-527 (including its C-degron) can also bind to the catalytic Nt-domain. The resulting conformation of Chk1 1-527 is inactive as a kinase and relatively long-lived, since the catalytic Nt-domain sterically sequesters C-degron. An induced (e.g., through a regulatory phosphorylation) dissociation of Ct-domain from Nt-domain activates the catalytic Nt-domain and also exposes the C-degron of Chk1. Thus, activation of Chk1 kinase would make it, simultaneously, a short-lived protein.